2019
DOI: 10.1021/acs.inorgchem.9b00266
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of Transition-Metal Dinitrosyl Complexes. A Molecular Orbital Rationale for the Attracto and Repulso Conformations

Abstract: Transition metal dinitrosyl complexes constitute a fairly large class of compounds, exemplified by some 500 structures in the Cambridge Structural Database. While many of the complexes exhibit a claw-like cis-attracto conformation, a handful of them exhibit a peculiar repulso conformation, in which the two NO groups are splayed outward and away from each other. Surprisingly, no computational study to date has attempted to explain the existence of these two limiting conformations of cis-dinitrosyl complexes. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 66 publications
1
5
0
2
Order By: Relevance
“…Chart summarizes the structure-characterized mononuclear {Fe­(NO) 2 } 9 /{Fe­(NO) 2 } 10 , dinuclear {Fe­(NO) 2 } 9 -{Fe­(NO) 2 } 9 /{Fe­(NO) 2 } 9 -{Fe­(NO) 2 } 10 /{Fe­(NO) 2 } 10 -{Fe­(NO) 2 } 10 , and tetranuclear [{Fe­(NO) 2 } 9 ] 4 DNICs discussed in this Forum Article. On the basis of the single-crystal X-ray structure of DNICs available in the Cambridge Crystallographic Data Centre (CCDC) database, classical DNICs with different types of supporting ligands and alternative redox levels feature an attracto conformation for the DNIU [Fe­(NO) 2 ] and a tetrahedral geometry for the Fe center [molecular orbital (MO) rationale for the attracto and repulso conformations for transition-metal dinitrosyl complexes was communicated recently] . Spectroscopic discriminations of these different types of DNICs by EPR spectroscopy, infrared (IR) spectroscopy, Fe/S K-edge X-ray absorption near-edge spectroscopy, and 15 N NMR were reviewed elsewhere .…”
Section: Results and Discussion: Bonding Nature And Electronic Struct...mentioning
confidence: 99%
See 1 more Smart Citation
“…Chart summarizes the structure-characterized mononuclear {Fe­(NO) 2 } 9 /{Fe­(NO) 2 } 10 , dinuclear {Fe­(NO) 2 } 9 -{Fe­(NO) 2 } 9 /{Fe­(NO) 2 } 9 -{Fe­(NO) 2 } 10 /{Fe­(NO) 2 } 10 -{Fe­(NO) 2 } 10 , and tetranuclear [{Fe­(NO) 2 } 9 ] 4 DNICs discussed in this Forum Article. On the basis of the single-crystal X-ray structure of DNICs available in the Cambridge Crystallographic Data Centre (CCDC) database, classical DNICs with different types of supporting ligands and alternative redox levels feature an attracto conformation for the DNIU [Fe­(NO) 2 ] and a tetrahedral geometry for the Fe center [molecular orbital (MO) rationale for the attracto and repulso conformations for transition-metal dinitrosyl complexes was communicated recently] . Spectroscopic discriminations of these different types of DNICs by EPR spectroscopy, infrared (IR) spectroscopy, Fe/S K-edge X-ray absorption near-edge spectroscopy, and 15 N NMR were reviewed elsewhere .…”
Section: Results and Discussion: Bonding Nature And Electronic Struct...mentioning
confidence: 99%
“…Spectroscopic and computational insights, moreover, rationalized the synthetic cycles for NO-to-N . 32 Spectroscopic discriminations of these different types of DNICs by EPR spectroscopy, infrared (IR) spectroscopy, Fe/S K-edge X-ray absorption near-edge spectroscopy, and 15 N NMR were reviewed elsewhere. 30 In the following sessions, we will review the spectroscopic and computational insights into the bonding nature within the [Fe(NO) 2 ] unit and the electronic structure of classical DNICs, whereas the study of metallothiolate-bound DNICs is reported in other literature.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work, Ghosh and Conradie classified dinitrosyl structures in terms of electronic and geometrical parameters. [14] 1 follows their rules for an {M(NO) 2 } 10 (M = 4d or 5d element) species with its large NÀ RuÀ N angle and the "repulso" arrangement of the nitrosyls (which means that the slight deviation of the RuÀ NÀ O function from linearity results in an outward tilt of both NO ligands). Due to the only small deviation of the RuNO angle from 180°, 1 is an example of a dinitrosyl with two linear MNO functions.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Erst vor Kurzem klassifizierten Ghosh und Conradie Dinitrosylstrukturen nach elektronischen und geometrischen Parametern. [14] 1 folgt ihren Regeln für Spezies des Typs {M(NO) 2 } 10 (M = 4d-oder 5d-Element) mit seinem großen NÀ RuÀ N-Winkel und der "repulso"-Anordnung der Nitrosylliganden (was bedeutet, dass die geringfügige Abweichung der RuÀ NÀ O-Funktionen von der Linearität einen kleinen Knick nach außen ergibt.) Wegen der nur geringen Abweichung des RuNO-Winkels von 180°ist 1 ein Beispiel eines Dinitrosyls mit zwei linearen MNO-Funktionen, kurz: 1 ist eine (l-NO-kN) 2 -Spezies.…”
Section: Ergebnisse Und Diskussionunclassified
“…Erst vor Kurzem klassifizierten Ghosh und Conradie Dinitrosylstrukturen nach elektronischen und geometrischen Parametern [14] . 1 folgt ihren Regeln für Spezies des Typs {M(NO) 2 } 10 (M = 4d‐ oder 5d‐Element) mit seinem großen N−Ru−N‐Winkel und der “repulso”‐Anordnung der Nitrosylliganden (was bedeutet, dass die geringfügige Abweichung der Ru−N−O‐Funktionen von der Linearität einen kleinen Knick nach außen ergibt.)…”
Section: Ergebnisse Und Diskussionunclassified